Corpus d'extraits musicaux: indices relatifs à la familiarité, à l'âge d'acquisition et aux évocations verbales - PERETZ, ISABELLE; BABAÏ, MYRIAM; LUSSIER, ISABELLE; HÉBERT, SYLVIE; GAGNON, LISE (Canadian journal of experimental psychology, 1995)
L'objectif du présent travail est d'obtenir auprès d'étudiants universitaires francophones une estimation de trois indices, soit leur familiarité avec divers extraits musicaux, l'âge auquel ces extraits ont été acquis et les paroles qu'ils évoquent. Ces étudiants entendent 144 extraits musicaux puisés dans le répertoire présumé partagé par tous les québécois de langue française. Le principal apport de ce travail est de fournir un outil original d'étude de la perception et de la mémoire auditives. Par ailleurs, l'analyse des paroles évoquées par les airs entendus se révèle riche en enseignements. Notamment, lorsque la récupération des paroles est partielle, les sujets tendent à combler les lacunes avec des paroles qui respectent le sens et la structure temporelle de la chanson originale. Ce procédé de rappel corrobore la thèse voulant que la musique serve d'aide-mémoire à la transmission d'informations. The objective of the present study was to establish estimates of familiarity, of age of acquisition, and of verbal associations in relation to 144 musical excerpts drawn from the repertoire of tunes that is expected to be shared by all French-speaking Québec university students. The excerpts were synthesized monophonic lines (which can be found in Appendix B ) that were tape recorded. A first group of 60 university students were required to indicate their degree of familiarity (on a 5-point scale) with each excerpt and the age period at which they learned the excerpt. A second group of 60 students indicated whether the original tune was vocal or instrumental as well as the first words that came to mind. In each group, half the subjects were presented with the 144 excerpts in a different order. Overall, the material was found to be highly familiar and to have been mostly learned between the ages of 5 and 15. Most of the excerpts were easily categorized as vocal or instrumental with the exception of 26 excerpts, which were accordingly classified as ambiguous. Finally, 57% of the excerpts elicited verbal responses. There was a high level of agreement in some of the verbal responses provided, referred to as dominant responses. In contrast, 21 excerpts gave rise to very little verbal recall, hence specifying a subset of "purely" musical material. All indices of familiarity, of acquisition age, and of verbal responses (specifying the overall rate of verbal responding, the content of the dominant response as well as its frequency of occurrence) are provided for each excerpt in Appendix A. Finally, the most interesting aspect of the present study was revealed by the analysis of the errors in verrbal recall. Subjects tended to fill in missing elements by words that fitted the meaning of song lyrics as well as the temporal structure of the music. For instance, instead of providing "MON BEAU SAPIN", subjects would provide " mon grand sapin ". The use of such a procedure is consistent with the notion that music serves as a memory aid which facilitates the communication of news and ideas.